Penerapan Psak 69: Agrikultur Atas Aset Biologis Pada Pt. Sampoerna Agro Tbk - Pratama, Ahdika Viary; Ekowati , Wiwik Hidajah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This study aims to find out how the application of PSAK 69: Agricultural accounting for biological assets at PT. Sampoerna Agro Tbk. This study uses a qualitative research method with a case study approach. The data used is in the form of company financial reports published on company websites and IDX websites. The problem of this research is changing the accounting treatment of biological assets due to the enactment of PSAK 69: Agriculture. The results showed that the recognition of agricultural products as biological assets was in accordance with KKPK: 4.37; KKPK:4.44; and PSAK 69 par 10. Measuring product value based on fair value using a market approach and grouping agricultural products according to the attributes applied to the estimated product volume is in accordance with PSAK 69 Par 13 and Par 15. Presentation of biological assets in the current asset classification is in accordance with PSAK 1 par 66 and PSAK 69 par 5. The classification of biological assets as current assets is in accordance with PSAK 1 par 66 and PSAK 69 par 5. PT. Sampoerna Agro Tbk has applied the biological asset accounting treatment contained in PSAK 69: Agriculture to the company's biological assets. Abstrak This study aims to find out how the application of PSAK 69: Agricultural accounting for biological assets at PT. Sampoerna Agro Tbk. This study uses a qualitative research method with a case study approach. The data used is in the form of company financial reports published on company websites and IDX websites. The problem of this research is changing the accounting treatment on biological assets due to the enactment of PSAK 69: Agriculture. The results showed that the recognition of agricultural products as biological assets was in accordance with KKPK: 4.37; KKPK:4.44; and PSAK 69 par 10. Measuring product value based on fair value using a market approach and grouping agricultural products according to the attributes applied to the estimated product volume is in accordance with PSAK 69 Par 13 and par 15. Presentation of biological assets in the current asset classification is in accordance with PSAK 1 par 66 and PSAK 69 par 5. The classification of biological assets as current assets is in accordance with PSAK 1 par 66 and PSAK 69 par 5. PT. Sampoerna Agro Tbk has applied the biological asset accounting treatment contained in PSAK 69: Agriculture to the company's biological assets.